Effects of energy gel ingestion on blood glucose, lactate, and performance measures during prolonged cycling - Kozlowski, K. F.; Ferrentino-DePriest, A.; Cerny, F. (The Journal of Strength and Conditioning Research, 2021)
Endurance athletes have long used carbohydrate supplementation during prolonged exercise (most recently with energy gels) to enhance performance. The purpose of this study was to determine the effect of carbohydrate energy gel ingestion schedules (e.g., manufacturer's recommendations vs. a more frequent ingestion schedule) during 2 hours of steady-state cycling exercise on (a) blood glucose, (b) blood lactate, and (c) performance of a subsequent 15-minute time trial (TT). Ten trained cyclists (5 men and 5 women, mean age = 28.4 ± 3.66 years; body mass = 68.9 ± 10.63 kg; and Vo2max = 54.57 ± 9.45 mlO2/kg/min) performed 3 exercise trials in a randomized order. One gel was ingested 15 minutes before exercise during all trials. The 3 experimental trials included gel ingestion every 30 minutes (T1), every 45 minutes (T2) during exercise, and no gel ingested during exercise (T3). Subjects cycled at 70% of Vo2max for 2 hours, followed by a 15-minute fixed gear TT. The blood glucose level at 60 minutes of exercise was higher during T1 (125.5 ± 30.96 mg/dl) and T2 (127.6 ± 14.82 mg/dl) compared with T3 (102.8 ± 15.85 mg/dl). Time trial distance was significantly greater for T1 (7.56 ± 0.77 km) and T2 (7.16 ± 0.92 km) than T3 (6.69 ± 0.74 km) (p = 0.003) with moderate to strong effect sizes between trials. There were no differences in blood lactate concentrations across trials. Ingestion of energy gels during prolonged cycling elevates blood glucose levels and enhances subsequent performance, whereas a more frequent ingestion elicits additional performance benefits.